Redesign Mata Bor Tanah Untuk Pembuatan Lubang Biopori Di Desa Puron, Kecamatan Bulu, Kabupaten Sukoharjo - Zainal Arifin; Dominicus Danardono Dwi Prija Tjahjana; Rendy Adhi Rachmanto; Suyitno Suyitno; Singgih Dwi Prasetyo; Trismawati Trismawati (Mekanika, 2020)
The lack of rainfall and the absence of catchment areas are the main factors of the lack of water in Puron Village. Making biopori becomes solutive because it is useful for water absorption, reducing standing water, composting containers, and fertilizing the soil. Artificial biopores are made by making holes in the ground using tools such as crowbars or using ground drilling machines. The use of aids model adapted to the drill bit based on the state of the soil contour. This research is focused on classifying drill bits and redesigning which is in accordance with the condition of the soil environment in Puron Village, Bulu District, Sukoharjo Regency. So that biopori holes can be created more effectively and efficiently. The research method was carried out through the classification of tool drill bits through the house of quality product (HOQ) and redesign using Autodesk Fusion 360 software application. It was found that the design with a screw drill model with a pointed spiral has a high product quality value and can applied in puron Village. The design of the drill bit by adjusting the contours of the Puron Village can make a 100 mm diameter biopori hole. The design specifications of the drill bit with steel cast with 12 spiral plates with a length of 1300 mm with a diameter of 115 mm can be driven with a 10 HP engine. The design results have maximum stress, displacement, reaction force and strain of 3.62 MPa, 0.00081 mm, 0.35 N, and 0.000015.